(untitled) (Productivity, 2020)
The purpose of the research conducted is to Analyze Cash Flow Reports at PT. United Tractors, Tbk. This research uses a quantitative approach. Data collection uses documentation methods namely data that has been documented by the company and library guidelines. Based on the results of data analysis, the conclusion is that the Cash Flow Report of PT. United Tractors, Tbk is good enough. Based on the results of the study can be recommended suggestions: 1. Basically cash is the most liquid assets in the company because cash flow is the life of every company. It would be nice if the company’s management not only focused its assets only on accounts receivable, but also on cash. 2. The company is expected to be able to maintain and improve the quality of its management, especially in regulating net cash flow. 3. In preparing financial statements, especially cash flow statements should be used as reference material for company leaders to determine the extent of company performance that has been carried out and for management considerations in making decisions and policies that will be taken in the following years.